Protection Of Consumer Rights In KPR Agreements With Buy Back Guarantee Clauses (Case Study of Decision Number 9/Pdt.G/2021/PT.BTN) - Assyfa Putri Sonya; Suherman (KRTHA BHAYANGKARA, 2024)
Home Ownership Credit (KPR) agreements with buy-back guarantee clauses are increasingly used by developers to provide additional assurance for consumers. However, the implementation of these clauses often leads to ambiguity in consumer rights and legal protection. This research aims to analyze the legal protection of consumer rights in KPR agreements with buy-back guarantee clauses, focusing on the analysis of Decision Number 9/Pdt.G/2021/PT. BTN. Using a normative juridical method with a case study approach, the research highlights the inefficiency of buy-back guarantee clauses in providing effective protection, especially concerning refund rights in cases of developer default. The study emphasizes the importance of strengthening regulations and legal protections in KPR agreements to ensure consumer legal certainty. The findings indicate that consumers frequently lack clarity on their rights, leading to potential exploitation. Furthermore, the study emphasizes the necessity of strengthening regulations and legal protections within KPR agreements to ensure consumer legal certainty. The clauses can be increased transparency and comprehensive information disclosure to empower consumers and uphold their rights effectively. Enhanced a legal safeguards are essential for enabling consumers to confidently navigate KPR agreements, thereby fostering trust in the housing finance sector and ensuring their rights are effectively protected.